Unveiling the risks and critical mechanisms of polyhexamethylene guanidine on the antibiotic resistance genes propagation during sludge fermentation process. (September 2022) - Wang, Feng; Wei, Du; Zhang, Le; Huang, Wenxuan; Fang, Shiyu; Cheng, Xiaoshi; Cao, Jiashun; Wu, Yang; Su, Yinglong; Luo, Jingyang
Graphical abstract: Highlights: PHMG prompt the ARGs spread and alter distribution patterns of ARGs. PHMG increased cell permeability and MGEs that benefit the ARGs release and HGT. Potential ARGs hosts ( i.e. Burkholderia and Aeromonas ) are enriched in PHMG reactor. PHMG induce to the upregulation of metabolic pathways related with ARGs propagation. Microbial community was the predominant factor contributing to ARGs propagation. Abstract: This study mainly investigated the environmental risks of polyhexamethylene guanidine (PHMG) occurred in waste activated sludge (WAS) on the antibiotic resistance genes (ARGs) spread during anaerobic fermentation, and disclosed the critical mechanisms. The total ARGs abundance was increased by 32.2–46.4% at different stressing levels of PHMG. The main resistance mechanism categories of ARGs shifted to the target alternation and efflux pump. PHMG disintegrated WAS structure and increased the cell permeability, which benefitted the mobile genetic elements (MGEs) release and horizontal transfer of ARGs. Besides, PHMG induced the enrichment of potential ARGs hosts ( i.e., Burkholderia, Bradyrhizobium and Aeromonas ). Moreover, PHMG upregulated the metabolic pathways ( i.e., two-component system, quorum sensing, and ATP-binding cassette transporters) and critical genes expression ( i.e., metN, metQ, rpfF, rstA and rstB ) related with ARGs generation and dissemination. Structural equation model analysis revealed that microbial community structure was the predominant contributor to the ARGs propagation.